Esensi Meditasi Terhadap Spritualitas Umat Buddha - Ulfah, Siti Maria; Octaviana, Dilla Nur; Aqila, Muhammad (AL-ADYAN, 2019)
Along with the development of technology and information advances can no longer be denied. Increasing needs of life make humans do various ways to meet their needs.  However, at its peak humans are at a saturation point that tends to ignore the values of spirituality and religious teachings. Therefore they need something that can improve their spirituality one of them by meditation. This study aims to identify the effect of meditation on Buddhist spirituality in undergoing various problems of daily life. This research uses a qualitative research approach with the method used is the method of observation, interviews and literature studies with descriptive analysis methods. The results showed that meditation has a goal that can improve human spirituality, especially Buddhists. In addition, meditation also provides benefits and a great influence on the body and spirit of Buddhists in a way that has been arranged in such a way.